Fodors 89 Israel. - Rogoff, Mike (New York Fodors Travel Publications, 1989)
Israel, indeed tnhe Middle East as a whole, is in so constant a state of flux that it can be hard for a daily newspaper to chart the myriad shifts and changes of this volatile region, let alone an annually revised guide book.
Keywords: Country Studies